Model Pembelajaran Yang Dapat Menumbuhkan Sikap Berpikir Kritis Pada Siswa - Hendra Agustina; Zaenal Abidin (Peneliti.net, 2022)
Critical thinking ability is a high-level thinking skill that is able to increase students' ability to be more active in critical thinking, therefore critical thinking skills are needed because students who think critically will be able to think according to the experience that students can, answer problems well and can make decisions according to what students find . The purpose of this study is to identify the factors that influence critical thinking attitudes. A literature search was conducted on Google scholar by using the keyword “critical thinking attitude. This research tracing strategy includes the type of discovery learning model research where in this model students learn to find and find concepts independently for further research, it is necessary to do other research with other models to determine the effectiveness and practicality of the model to improve critical thinking disposition and skills. critical thinking by using qualitative methods (meta-synthesis). This research is a comparative causal research where this research is a quantitative research designed with a correlational design. Where the sample used was 70 students who were selected randomly while the data collection method used in this study was a survey using a questionnaire. The data analysis technique used to test the hypothesis is product-moment correlation technique and multiple regression correlation analysis.